Structural response and fatigue assessment of a small vertical axis wind turbine under stationary and non-stationary excitation. (June 2021) - Orlando, Andrea; Pagnini, Luisa; Repetto, Maria Pia
Abstract: The paper discusses the response and fatigue damage of the supporting tower of a small vertical axis wind turbine subject to stationary and non-stationary excitation due to wind, turbine rotation, emergency stop and start. Using in-field measurements and the Hot Spot Stress Approach, the study analyses a number of aspects that are usually disregarded in design verifications. The results highlight the importance of the detail modeling, the fundamental role played by the non-stationary conditions and the errors committed when using conventional models of the load. The emphasis of this paper is put on two main aspects: the use of full scale data and the detection of isolated events of non-stationary vibrations, the effects of which can be disregarded when using stress time-histories of 10 min - 1 h. Highlights: Importance of correct characterization of FAT category of the structural details. Non-stationary loads give rise to critical conditions for fatigue crack propagation. Crucial role of low-frequency stress cycles in fatigue damage. Uncertain estimate of the fatigue damage when using few 10-min stress time-histories. Limits of current standard methods for small wind turbine design.